ANALISIS PENERAPAN OPERATING LEASE BERDASARKAN PSAK. NO 30 PADA PT. YOSEPHA MANOKWARI - Jones, Tifani; Pangemanan, Sifrid S.; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
PT. Yosepha is a company engaged in the services of contractors and suppliers who also have additional business to support the company and increase profits are rental of fixed assets. Type of lease applied by PT. Yosepha is an operating lease. Operating lease is an ordinary lease, whereby at the end of the lease term there is no option rights for the lessee or heavy equipment leased to remain owned by PT.Yosepha. In the lease activities conducted by PT.Yosepha must comply with the applicable accounting standards set out in statement of financial accounting standards number 30, because it is very impact on the financial statements generated by PT.Yosepha. The purpose of this study is to determine whether the application of lease accounting on PT.Yosepha has been in accordance with the statement of financial accounting standards number 30 and how the effect on the financial statements. The method used in this research is descriptive study. The result of the research is where PT.Yosepha has not totally applied lease accounting in this case that is operating lease in accordance with statement of financial accounting standards number 30 Â because there is a mistake in the disclosure and reporting so that the resulting financial statements are not clear so that it is not in accordance with applicable standardsKeywords: Operating Lease, Statement of Financial Accounting Standards Number 30, Financial Statement